Bis(2-amino-4-methyl-6-oxo-3,6-dihydropyrimidin-1-ium) sulfate monohydrate - Soudani, Sarra (International Union of Crystallography, 2014)
In the title hydrated molecular salt, 2C(5)H(8)N(3)O(+)·SO(4) (2−)·H(2)O, the components are linked by N—H⋯O(s) and O(w)—H⋯O(s) (s = sulphate, w = water) hydrogen bonds, generating a layer by a+b+c and 2a−b translations. The cations are arranged nearly in parallel and show displaced π–π stacking centroid–centroid distance = 4.661 (2) Å between adjacent layers.